Bilateral distal femoral trochlear block migration after medial patellar luxation surgery in a dog - Danielle M. McNabney; Soroush Irandoust; Kenneth Bruecker; Peter Muir (Veterinary Research Communications, 2026)
The objective of this study was to describe management of a 2-year-old neutered male mixed breed dog with bilateral trochlear block recession migration with unilateral revision surgery. This is a rarely reported complication of a common surgical procedure. A 3D model segmented from a computed tomography scan using Mimics was performed before surgery to help determine whether surgical reduction of the osteochondral trochlear block fragments was feasible and preoperative press fit was acceptable. Subsequently, the trochlear block fragment in the left stifle was surgically reduced. During surgery, the osteochondral fragment was maintained in reduction with a transcondylar Kirschner wire because of imperfect press fit. The right stifle with trochlear block migration was treated medically. Short-term follow-up examination at 5 and 8 weeks revealed improvement in lameness after surgery. 3D modeling was also used to investigate potential underlying causes for bilateral block recession migration which was determined to be multi-factorial with excessive sulcoplasty depth being an important reason promoting risk of migration. During planning for femoral trochlear block recession sulcoplasty, it is important for the cut to be deep enough to help minimize risk of reluxation of the patella. However, press-fit of the osteochondral fragment is impaired when the depth of the recession sulcoplasty is excessive.

Assessing threats and conservation action using population viability analysis for the Critically Endangered Grenada Dove Leptotila wellsi - Catherine Peters; Anna Muir; Charlotte Hosie; Howard Nelson; Matthew Geary (Journal for Nature Conservation, 2026)

Quantification of the difference in hounsfield units of an electron density phantom between a conventional and standing computed tomography machine - Catherine Beck; Ashleigh V. Morrice-West; Peter Muir; Peta L. Hitchens; R. Christopher Whitton (Veterinary Research Communications, 2025)
In human CT imaging, opportunistic calculation of bone mineral density (BMD) is used to screen for osteoporosis, where BMD is estimated by Hounsfield Units (HU). There is potential to use HU for estimation of BMD in veterinary imaging. However, HU values can vary between different machines and over time. We undertook a serial measurements study to determine (1) the extent of the difference of the mean HU and noise (HU standard deviation) of eight regions of interest (ROI) of an electron density phantom scanned on two CT machines, a Siemens CT (conventional) machine and the Equina by Asto CT (standing) machine; and (2) to determine if the HU values obtained on each machine differed over time. The mean HU from 30 scans of an electron density phantom were generated from each of the two CT machines ( N = 60; conventional and standing). Differences between machines were assessed using a linear mixed effects model. The mean HU of each positive value ROI from the conventional machine was decreased compared with the standing machine ( P < 0.001) and the difference was greatest for the denser phantom inserts. A calibration curve equation utilising the four bone-equivalent insert plugs of the phantom, with known calcium hydroxyapatite (CaHA) concentration, was generated using linear regression to represent CaHA, and therefore BMD, for the conventional machine (CaHA = -29.58 + 0.98xROI mean ) and the standing machine (CaHA = -54.53 + 0.95xROI mean ). For opportunistic calculation of BMD from HU in horses, the differences in HU observed between different CT machines warrants calibration of HU using a bone equivalent phantom.

Total knee replacement in a dog with an articular epiphyseal medial condylar fracture of the distal femur, a case report - Brent R. Fink; Laurent P. Guiot; Peter Muir (Veterinary Research Communications, 2025)

Stabilization of coxofemoral luxation in macropods using the Tightrope® system: 3 cases (2016–2023) - Greta Doden; Hugo A. Gonzalez-Jassi; Gregory Yoast; Katharine Hausmann; Faolain Barrett; Grayson Doss; Anna Martel; Peter Muir; Gary Spodnick; Tania Perez Jimenez; Mark Rochat; João Brandão (Journal of Exotic Pet Medicine, 2025)

Years late and millions short: A predictive audit of economic impacts for coal mines in British Columbia, Canada - Rosemary Collard; Jessica Dempsey; Bruce Muir; Robyn Allan; Abigail Herd; Peter Bode (Environmental Impact Assessment Review, 2023)

A novel method to optimise the utility of underused moulted plumulaceous feather samples for genetic analysis in bird conservation - Catherine Peters; Howard Nelson; Bonnie Rusk; Anna Muir (Conservation Genetics Resources, 2020)
Non-invasive sampling methods are increasingly being used in conservation research as they reduce or eliminate the stress and disturbance resulting from invasive sampling of blood or tissue. Here we present a protocol optimised for obtaining usable genetic material from moulted plumulaceous feather samples. The combination of simple alterations to a ‘user-developed’ method, comprised of increased incubation time and modification of temperature and volume of DNA elution buffer, are outlined to increase DNA yield and significantly increase DNA concentration (W = 81, p < 0.01, Cohens’s d = 0.89). We also demonstrate that the use of a primerless polymerase chain reaction (PCR) technique increases DNA quality and amplification success when used prior to PCR reactions targeting avian mitochondrial DNA (mtDNA). A small amplicon strategy proved effective for mtDNA amplification using PCR, targeting three overlapping 314–359 bp regions of the cytochrome oxidase I barcoding region which, when combined, aligned with target-species reference sequences. We provide evidence that samples collected non-invasively in the field and kept in non-optimal conditions for DNA extraction can be used effectively to sequence a 650 bp region of mtDNA for genetic analysis.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of urbanization on the population structure of freshwater turtles across the United States - David R. Bowne; Bradley J. Cosentino; Laurel J. Anderson; Christopher P. Bloch; Sandra Cooke; Patrick W. Crumrine; Jason Dallas; Alexandra Doran; Jerald J. Dosch; Daniel L. Druckenbrod; Richard D. Durtsche; Danielle Garneau; et al. (Conservation Biology, 2018)
Landscape‐scale alterations that accompany urbanization may negatively affect the population structure of wildlife species such as freshwater turtles. Changes to nesting sites and higher mortality rates due to vehicular collisions and increased predator populations may particularly affect immature turtles and mature female turtles. We hypothesized that the proportions of adult female and immature turtles in a population will negatively correlate with landscape urbanization. As a collaborative effort of the Ecological Research as Education Network (EREN), we sampled freshwater turtle populations in 11 states across the central and eastern United States. Contrary to expectations, we found a significant positive relationship between proportions of mature female painted turtles ( Chrysemys picta ) and urbanization. We did not detect a relationship between urbanization and proportions of immature turtles. Urbanization may alter the thermal environment of nesting sites such that more females are produced as urbanization increases. Our approach of creating a collaborative network of scientists and students at undergraduate institutions proved valuable in terms of testing our hypothesis over a large spatial scale while also allowing students to gain hands‐on experience in conservation science.

Islands in the ice stream: were spawning habitats for native salmonids in the Great Lakes created by paleo‐ice streams? - Stephen C Riley; Thomas R Binder; Taaja R Tucker; John Menzies; Nick Eyles; John Janssen; Andrew M Muir; Peter C Esselman; Nigel J Wattrus; Charles C Krueger (Fish and Fisheries, 2017)
Lake trout Salvelinus namaycush , lake whitefish Coregonus clupeaformis and cisco Coregonus artedi are salmonid fishes native to the Laurentian Great Lakes that spawn on rocky substrates in the fall and early winter. After comparing the locations of spawning habitat for these species in the main basin of Lake Huron with surficial substrates and the hypothesized locations of fast‐flowing Late Wisconsinan paleo‐ice streams, we hypothesize that much of the spawning habitat for these species in Lake Huron is the result of deposition and erosion by paleo‐ice streams. This hypothesis may represent a new framework for the identification and protection of spawning habitat for these native species, some of which are currently rare or extirpated in some of the Great Lakes. We further suggest that paleo‐ice streams may have been responsible for the creation of native salmonid spawning habitat elsewhere in the Great Lakes and in other glaciated landscapes.

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Coupled Chemical Shrinkage and Consolidation: Some Benchmark Solutions - David Muir Wood; James Peter Doherty (Transport in Porous Media, 2014)

Multi-species evolutionary dynamics - Joseph Apaloo; Peter W Muir; John W Hearne (Evolutionary Ecology, 2005)